Routine Health Facility and Community Information Systems: Creating an Information Use Culture - Lippeveld, Theo (Glob Health Sci Pract, 2017)
Substantial progress has been made to strengthen health information systems, with most efforts focusing on digitization, improving data quality and analysis, and identifying problems. But the ultimate goal is using information to solve problems, which requires building an information use culture over time. How? Human-centered design, role modeling by senior managers in use of data, and incentive-based systems hold considerable promise.